2012
DOI: 10.1002/cite.201100178
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneously Catalyzed Production of Furfural from Xylose

Abstract: The results of the dehydration of C5-raw material to obtain furfural via heterogeneous catalysis in water are discussed. Furfural has the potential to substitute fossil compounds on a large scale for polymers, solvents, fine chemicals and finally fuels. Industrial catalysts were reviewed and new catalysts were synthesized. The main difference to recent work is the abdication of supercritical fluids, organic solvents, phase modifiers and ionic liquids. With this also the contamination of the product is prevente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The annual production of furfural reached 0.5-1 million tonnes. 250,251 Recently, a route for the synthesis of PTA from furfural was reported by Tachibana Y. et al 252 As shown in Scheme 11, this route includes six steps, namely, oxidation of furfural to fumaric acid and maleic acid, dehydration of fumaric acid and maleic acid to maleic anhydride, Diels-Alder (DA) reaction of anhydrous maleic acid and furan to DA adduct, dehydration of the DA adduct to phthalic anhydride, hydrolysis of phthalic anhydride to dipotassium phthalate, transfer reaction and acidification of dipotassium phthalate to terephthalic acid. By integrating these steps, PTA could be synthesized from furfural with 100% biobased carbon as measured by accelerator mass spectroscopy.…”
Section: Synthesis Of Pta From Furfuralmentioning
confidence: 99%
“…The annual production of furfural reached 0.5-1 million tonnes. 250,251 Recently, a route for the synthesis of PTA from furfural was reported by Tachibana Y. et al 252 As shown in Scheme 11, this route includes six steps, namely, oxidation of furfural to fumaric acid and maleic acid, dehydration of fumaric acid and maleic acid to maleic anhydride, Diels-Alder (DA) reaction of anhydrous maleic acid and furan to DA adduct, dehydration of the DA adduct to phthalic anhydride, hydrolysis of phthalic anhydride to dipotassium phthalate, transfer reaction and acidification of dipotassium phthalate to terephthalic acid. By integrating these steps, PTA could be synthesized from furfural with 100% biobased carbon as measured by accelerator mass spectroscopy.…”
Section: Synthesis Of Pta From Furfuralmentioning
confidence: 99%
“…The remaining solids are hydrolyzed to dissolved glucose and solid lignin. These hemicellulose-rich extracts can be used as a substrate for fermentation to a variety of products [7,8], the conversion to furfural [9][10][11][12], and the purification of components such as xylooligosaccharides [6]. Often, separate hemicellulose and glucose valorization pathways are deemed too expensive.…”
Section: Introductionmentioning
confidence: 99%